2007
DOI: 10.1021/ef700464s
|View full text |Cite
|
Sign up to set email alerts
|

Products and Global Weight Loss Rates of Wood Decomposition Catalyzed by Zinc Chloride

Abstract: Motivated by the production of fine chemicals and the improvement of flame retardance properties, experiments have been performed with a fixed-bed reactor to investigate the catalytic action exerted by zinc chloride on fir wood pyrolysis (catalyst concentrations between 0 and 16% on a dry wood basis and heating temperatures between 650 and 900 K). It has been observed that this Lewis acid acts as a dehydrating and cross-linking agent promoting the formation of char and water with total yields up to about 73%. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
83
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(97 citation statements)
references
References 41 publications
12
83
2
Order By: Relevance
“…2), furfural yields remain quite low -about 0.5 wt.% on a catalyst-free basis -whatever the catalyst. At first sight, this result does not fit those of Di Blasi et al [39] reporting a high catalytic effect of ZnCl 2 towards furfural formation from impregnated fir wood. This difference might be explained by the chemical differences between hemicelluloses from softwood and from hardwood and by the fact that a too high ZnCl 2 amount can reduce the catalytic effect [14,39].…”
Section: Catalytic Effects Of Metal Salts On Bio-oil Compositionscontrasting
confidence: 95%
“…2), furfural yields remain quite low -about 0.5 wt.% on a catalyst-free basis -whatever the catalyst. At first sight, this result does not fit those of Di Blasi et al [39] reporting a high catalytic effect of ZnCl 2 towards furfural formation from impregnated fir wood. This difference might be explained by the chemical differences between hemicelluloses from softwood and from hardwood and by the fact that a too high ZnCl 2 amount can reduce the catalytic effect [14,39].…”
Section: Catalytic Effects Of Metal Salts On Bio-oil Compositionscontrasting
confidence: 95%
“…The introduction of aluminium titanate, titanium silicate, aluminium oxide colomba [26] or Sn-MCM-41 [27] could also increase the yield of anhydro sugars. As for furan ring derivatives, some acidic catalysts such as zinc chloride [13,28], sulfated metal oxides [29], are very effective. Di Blasi et al [25] observed that zinc chloride is a particularly effective catalyst (concentrations of 1%-6% and temperatures of 700-800 K) to maximize the yields of acetylfuran, 5-methyl-2-furaldehyde, and, especially, 2-furaldehyde for the pyrolysis of wood samples.…”
Section: Change Of Product Distribution Via Catalytic Effectsmentioning
confidence: 99%
“…A mechanism has been proposed for acid-catalyzed decomposition of LG to form the LGO, as shown in Fig.5 (Halpern et al, 1973). Various acid catalysts exhibited the capability to promote the LGO formation, such as the MgCl 2 and FeCl 3 (Klampfl et al, 2006), (NH 4 ) 2 SO 4 and (NH 4 ) 2 HPO 4 (Pappa et al, 2006;Di Blasi et al, 2007), CrO 3 and CrO 3 +CuSO 4 (Fu et al, 2008a), ZnCl 2 (Di Blasi et al, 2008), M/MCM-41(M=Sn, Zr, Ti, Mg, etc.) (Torri et al, 2009a).…”
Section: Levoglucosenonementioning
confidence: 99%